(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Recognizing that, beyond actions, a dramaturgy is also a work that weaves passions, this article proposes the body-that-writes as a practice of availability that precedes the text to come. To this end, it draws on the creation process of azevedo (2022-2023), a Portuguese literary publication, establishing connections with the theory of affection (Spinoza) and the notions of performative program (Fabião) and in operativity (Agamben).